Interculutral Polish-Chinese QQing - Elżbieta Gajek (Center for Open and Multimedia Eduacation of the University of Warsaw, 2012)
Working in tandem with the use of information and communication technologies is well-known and frequently used as a method of supporting learning of foreign languages in authentic communication. It is based on a constructivist approach to teaching. In the reported case study Polish and Chinese students discussed in English preprepared topics. The work shows the potential of e-learning at the micro level, as the language and intercultural task is implemented into an academic course without modification of the objectives and learning outcomes of the course. Evaluation carried out at the end of the project indicates that both groups perceived the task as a significant linguistic, cultural and personal experience. They stressed the importance of sharing "culture for culture" as the partner culture was new for most of them. The ability to talk and respond to information which was often strange, from the point of view of their own culture, allowed for learning intercultural competence ̔in action'.